Pijat Oketani dan Tekanan di Titik Akupresur GB-21 terhadap Produksi ASI pada Ibu Post Sectio Caesarea - Putri Permata Sari; Irna Nursanti; Giri Widakdo (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effectiveness of oketani massage and acupressure pressure of GB-21 on milk production in post-Caesarea section mothers. The research method used is quantitative research with a quasi-experimental research design, one group pre-posttest design. The results showed that the pressure on the acupressure point of GB-21 was sufficient based on mother and baby indicators. The statistical test results showed differences in milk production before and after pressure at the acupressure point of Gb-12 (p-value = 0.000). In conclusion, oketani massage is more effective in increasing milk production in group A, post section caesarea mothers compared to group B, the pressure at the acupressure point Gb-21 from infant indicators. Keywords: Gb-21 Acupressure, Breast Milk, Oketani Massage, Sectio Caesarea